Tambalan Nicole Hyala at Chris Tsuper : the Philippines'most popular DJs - Siy, Beverly; Hyala, Nicole; Tsuper, Chris (Mandaluyong City Anvil Publishing, Inc., 2013)
Excerpts from the popular radio program with the same title.
Keywords: Hyala, Nicole; Tsuper, Chris; Radio comedies -- Philippines